Perancangan Buku Cerita Anak Pop-Up â€œMari Berkebunâ€ - Divita, Monique Rizki (Bina Nusantara University, 2011)
The research purpose is to gather, collect, and analyze data which needed in creating children story book in pop-up technique, with visually interesting gardening theme to interact with children. The research method is by direct survey into the location, such as schools, children story bookstores, and libraries. Besides, the research will be through literature media like books, magazines and journals; also supported by references contain related topic, like internet. The expected result is that education and added value message could be sent and understood by the children through the story books. The children would acknowledge, love, and preserve nature through gardening. In conclusion, nowadays, visual communication media like story books with interesting visual could gain children?s interest. Therefore, by using pictured story book media in pop-up, it will facilitate the education process of introducing and preserving Mother Nature for children.